Education Review Office: An Agency for Assessment and Audit - Bhusal, Chandra Kanta (Education Review Journal, 2024)
A global trend of conducting assessment, audit, research and evaluation like activities to enhancing accountability of all sectors of education, more specifically of school education sector is in place. In general, an autonomous organization is designed to execute this kind of activities. In the context of Nepal, Education Review Office (ERO) was established under the Ministry of Education, Science and Technology (MOEST), to be developed as an agency for assessment and audit. It is mandated basically to conducting national assessment of student achievement (NASA) of school level students and performance audit (PA) of education entities and schools. This office started conducting large scale assessments namely NASA, and PA of concerned authorities and schools since its inception in 2010.This article has tried its best to inform the audience about ERO activities highlighting findings of NASA and PA, most specifically focusing on rights and duties of ERO as an agency for assessment and audit through the review and analysis of the ERO reports and related documents. It picturizes the NASA and PA efforts as well as all the concerned activities of ERO by analyzing most specifically NASA, PA reports data using descriptive and analytical procedures. Furthermore, it also highlights the historical background of ERO, finds out problems and challenges it has been facing and gives possible solutions to be carried out along with related policy arrangements for the betterment of assessment and audit practices as well as school education system of Nepal.